International Experience in Business Processes Improving on the Base of Architectural Approach - Fici, Luigi; Malyzhenkov, Pavel; Masi, Maurizio; Rossi, Fabrizio (Nepalese Journal of Management Science and Research, 2019)
Standardization is the pinnacle of the quality management instruments, which is vital for satisfying customer needs and ensuring sustainable development of business. The ISO 9001:2015 (Quality Management Systems, QMS) standard requires organizations to use the process approach. This paper proposes to use architectural approach for analysis and improvement of business processes for implementation of the ISO 9001:2015 standard.